The Impact of World Food Price on Domestic Inflation: Evidence from Sri Lanka - Anusha, P.; Pirasayiny, T.; Sivarajasingham, S. (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Food price contributes the largest share in the general price index in developing countries. Food prices have been increasing in Sri Lanka since 2003. The recent growth of global food prices affects the welfare of poor people, consumers and producers. In Sri Lanka large segment of the population spends more than 50 percent of their income on food; this study investigates and assesses how international food price surge affects domestic inflation process in Sri Lanka. The empirical statistical results are derived by using a battery of parametric and non-parametric econometric techniques using monthly data of price series for the period from 2003M1-2020M12. The Johansen’s co-integration analysis results confirm that global food prices and domestic prices are co-integrated therefore Sri Lankan government needs to develop a safety net program for the poor and a poverty reduction strategy. Policy attention needs to shift towards efforts to increase food production in Sri Lanka. The results of the study have various policy implications of monetary policy, food and agriculture policy and trade policy for Sri Lanka.